Peningkatan Kesadaran Hukum Masyarakat Melalui Kegiatan Sosialisasi Undang-Undang Bantuan Hukum Di Dusun I Desa Kuapan, Kecamatan Tambang, Kabupaten Kampar - Tibra Raradhini Armady; Radinka Syaqinah Adisty; Tita Felisha Sanjaya Putri; Satlah Indri Junita; Vebby Valentine; Dinda Kanya Dewi; Salsabilla Trisuci; Rahma Ardini; Rizky Ananda Hartanti Harahap; Samariadi Samariadi (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
Kuapan Village has several legal problems that often occur, such as theft, juvenile delinquency, and credit fraud. In village communities, often when legal problems arise they are afraid to take the legal problem to court. There are several factors that cause people to be afraid, one of which is a lack of legal awareness. Legal awareness can be interpreted as the awareness of a person or group of people regarding the applicable rules or laws. Legal awareness is very necessary for a society. This aims to ensure that order, peace, tranquility and justice can be realized in interactions between people. With the existence of the KUKERTA student work program in the form of counseling on Law Number 16 of 2011 concerning Legal Aid, the aim is to create awareness and compliance with laws and regulations for society so that every member of society is aware of and appreciates their rights and obligations as citizens and can realize them in life. daily. This legal counseling was carried out in Kuapan Village, Tambang District, Kampar Regency.